Knowledge of Parents about Bruxism in their Children - Calıskan DDS, PhD, Secil; Delikan DDS, MDs, Ebru; Ozcan-Kucuk DDS, MDs, Ayse (Odovtos - International Journal of Dental Sciences, 2019)
Objective: Bruxism is a jaw muscle activity disorder characterized by clenching or grinding of the teeth and can be seen in both children and adults. The purpose of this study is to evaluate the parental knowledge about bruxism in children. Methods: A cross-sectional study was conducted with 265 parents whose children were attended at University of Mersin pediatric dentistry and oral and maxillofacial surgery clinics. Children’s ages varied from 6 months to 16 years old. A 20-questioned questionnaire was used to collect the data. IBM SPSS Statistics 22 for statistical analysis (SPSS IBM, Turkey) program was used for the analysis. Results: A total of 265 parents (159 were female and 106 were male) participated in the study. The majority of the parents were between the ages of 31-40 (60.8%). The rate of clenching and grinding of teeth during sleep (21.5%) was higher than the rate when they were awake (7.2%). The ratio of the parents seeking treatment for their children because of this harmful habit was very low (3.8%). The majortiy of parents (37.7%) reported that they seek help from dentists. The participants believed that bruxism was associated with dental problems (33.6%) and emotional factors (32.8%). A significant difference was found between the educational background of the parents and the ability to define bruxism. Conclusion: Parents had inadequate knowledge about bruxism in children and this was mostly related to the educational background of the parents.